RESISTENSI PEREMPUAN DAN IDEOLOGI PENGARANG TERHADAP TRADISI-TRADISI DI PESANTREN - Kamila Adnani; Wening Udasmoro; Ratna Noviani (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Abstract: Gender issue in pesantren (or Islamic Boarding School) is a part of larger gender problem in Indonesia, either in education and in religion. The main indicator of this problem is vivid gap between males and females. This issue is actually not a new thing for there are a bunch of Indonesian novels serve it. Those novels touching pesantren in the theme usually put the women as a powerless, subordinated, inferior, marginalized person. However, the novel Perempuan Berkalung Sorban(PBS) tries to empower women. In the novel, the woman is portrayed as brilliant, brave, and also critical toward the pesantren hegemony such as: the power relation between santri (students) and kiai (teachers), the understanding on classical books (kitab kuning), social relation between men and women in pesantren ciircumstances, and many more. Kata Kunci: Resistensi, Ideologi, Perempuan, Pesantren